IDENTIFIKASI MORFOLOGI DAN HUBUNGAN KEKERABATAN TANAMAN PORANG (AMORPHOPHALLUS MUELLERY BLUME) DI KECAMATAN KUMPEH ULU KABUPATEN MUARO JAMBI - Lizawati Lizawati; Elis Kartika; Yulia Alia; Dedy Antony (Agric, 2023)
Porang (Amorphophallus muelleri Blume) is a group of tuber plants that are useful as food and medicine so that they have bright prospects for development. In Jambi Province, especially in Muaro Jambi Regency, porang plants are found growing wild among duku trees. This study aims to determine the morphological character of porang plants and to determine the level of diversity and kinship of porang plants found in Kumpeh Ulu District, Muaro Jambi Regency. The research was carried out from August to September 2021, in 18 villages located in the Kumpeh Ulu District. The research was conducted using a non-experimental descriptive method with proportionate stratified random sampling, and the sample was measured quantitatively and qualitatively. The morphological identification of porang plants from 18 villages in Kumpeh Ulu District showed similarities in bulbil shape, bulbil surface colour, bulbil surface texture, bulbil flesh colour, leaf shape and petiole colour. However, there were differences in leaf colour, tuber flesh colour, tuber surface texture and tuber shape.